Re-focusing agricultural research to deal with farmers' real issues - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Dr. Michael Hailu, Director, The Technical Centre for Agricultural and Rural Cooperation talks on significance of the conference, multi-stakeholder engagement and youth involvement in Agriculture. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/